The comparative analysis of the compressible plasma streams generated in QSPA from the various gases - Kozlov, A.N.; Drukarenko, S.P.; Seytkhalilova, E.I.; Solyakov, D.G.; Velichkin, M.A. (Вопросы атомной науки и техники, 2012)
The numerical research of streams dynamics in the channel and the compressible flows at the QSPA output is carried out for the plasma generated from hydrogen, helium, argon and xenon. The MHD equations in the one-fluid approach taking into account the final conductivity of medium, the heat conductivity and the effective losses of radiation energy underlie the numerical model of the two-dimensional axisymmetric plasma flows. Features of the compressible plasma streams generated from various gases are revealed.